Characteristics of the Mothers on Stunting Toddlers 12-36 Months West Bandung Regency, Indonesia - Elba, Fardila; Che Hassan, Hafizah; Umar, Nur Syazana (Faculty of Medicine Universitas Padjadjaran, 2024)
Objective: To determine the characteristics of respondents with stunted toddlers aged 12-36 months in the Batujajar and Cihampelas districts of West Bandung District.Methods: A case-control study with a pretest-posttest design was conducted from May to August 2022 in West Bandung Regency, Indonesia. The study included 124 mothers with stunted toddlers, who were divided into two groups - control and treatment - with 62 toddlers each, using simple random sampling.Result: The majority of children under the age of five in this study were female. In the case group, the majority of mothers were in the 20-29 age range (40.3%), while in the control group, the majority were in the 30-39 age range (38.7%). Most mothers in both the control and case groups had a high school education (41.8%). The majority of participating mothers were housewives (85.5%). Childcare was primarily provided by mothers, and most of the resource persons were also mothers.Conclusion: Based on the characteristics observed in this study, the majority of children under the age of five were female in both the case and treatment groups. Most mothers in both groups had a high school education, and the majority of participating mothers were housewives. Childcare was primarily handled by mothers, and most of the resource persons were also mothers.